UNDERSTANDING OF BASIC CONCEPTS FOR MASTERING COMPETENCES OF SCHOOL MATHEMATICS - Sondore, Anita; Krastiņa, Elfrīda; Daugulis, Pēteris; Drelinga, Elga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Mathematical competence as a universal and fundamental competence is essential for everyone as a problem solving and life quality improving tool. It is also essential for future teachers who will implement competence based teaching processes starting from elementary schools and preschools. The goal of this research is to discuss typical errors about certain basic mathematical concepts which are taught in school. Failure to grasp these concepts cause problems for learning subsequent mathematics courses and dealing with practical problems. This research will help to improve studies at university level. Experience analysis of university educators related to oral and written answers of students in tests is used in this research. Observations show that many errors get repeated year by year.